Toward a humanist justice the political philosophy of Susan Moller Okin - Satz, Debra; Reich, Rob. (New York ; Oxford : Oxford University Press, 2009)
Okin argued that liberalism, properly understood as a theory opposed to social hierarchies and supportive of individual freedom and equality, provided the tools for criticizing the substantial and systematic inequalities between men and women.
Conference proceedings.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Feminism -- Congresses; Women's rights -- Congresses; Equality -- Congresses; Justice -- Congresses; Liberalism -- Congresses; Okin, Susan Moller -- Political and social views -- Congresses